Fundamentals of pervasive information management systems - Kumar, Vijay, 1946- (John Wiley and Sons, Inc., 2013)
"Covering both mobile data and sensor data, this comprehensive text offers updated research on sensor technology, stream data processing, mobile database security, and contextual processing. Packed with exercises and examples, the book covers essential aspects of wireless communication and provides a thorough discussion about managing information on mobile database systems. In addition, the author addresses the integration of web and workflow with mobile computing and looks at the current state of research"--